Electronically Reconfigurable Photonic Switches Incorporating Plasmonic Structures and Phase Change Materials. Issue 20 (17th April 2022) - Farmakidis, Nikolaos; Youngblood, Nathan; Lee, June Sang; Feldmann, Johannes; Lodi, Alessandro; Li, Xuan; Aggarwal, Samarth; Zhou, Wen; Bogani, Lapo; Pernice, Wolfram HP; Wright, C David; Bhaskaran, Harish
Abstract: The ever‐increasing demands for data processing and storage will require seamless monolithic co‐integration of electronics and photonics. Phase‐change materials are uniquely suited to fulfill this function due to their dual electro‐optical sensitivity, nonvolatile retention properties, and fast switching dynamics. The extreme size disparity however between CMOS electronics and dielectric photonics inhibits the realization of efficient and compact electrically driven photonic switches, logic and routing elements. Here, the authors achieve an important milestone in harmonizing the two domains by demonstrating an electrically reconfigurable, ultra‐compact and nonvolatile memory that is optically accessible. The platform relies on localized heat, generated within a plasmonic structure; this uniquely allows for both optical and electrical readout signals to be interlocked with the material state of the PCM while still ensuring that the writing operation is electrically decoupled. Importantly, by miniaturization and effective thermal engineering, the authors achieve unprecedented energy efficiency, opening up a path towards low‐energy optoelectronic hardware for neuromorphic and in‐memory computing. Abstract : Light is uniquely suited to transport parallelized information and perform high‐speed computations. In this article, the authors have engineered a path for optical signal modulation, data storage and computation driven by electronics. By confining light to a nanoscale volume through plasmonic structures and by employing active phase‐change materials the authors demonstrate ultra‐low energy, non‐volatile switching with electrical and optical readout.